Oral bisphosphonates are associated with increased risk of subtrochanteric and diaphyseal fractures in elderly women: a nested case–control study - Erviti, Juan (BMJ Publishing Group, 2013)
OBJECTIVES: To evaluate the association between bisphosphonate use and the risk of atypical femoral fractures among women aged 65 or older. DESIGN: Nested case–control study. SETTING: General practice research database in Spain. EXPOSURES: Use of oral bisphosphonates before the occurrence of atypical fractures among cases or the corresponding index date among controls. Bisphosphonate use was categorised as ever versus never users. Ever users were divided according to the total time since first prescription. MAIN OUTCOME MEASURES: Cases were defined as women aged 65 years or older with a first diagnosis of subtrochanteric or diaphyseal fracture, recorded in the BIFAP database between 1 January 2005 and 31 December 2008, and with at least 1 year of follow-up before the index date. For each case, five age-matched and calendar-year-matched controls without a history of hip or atypical fracture were randomly selected from the database. STATISTICAL ANALYSIS: OR of atypical femoral fracture by bisphosphonate use was determined using conditional logistic regression. Models were adjusted for comorbidities and use of other medications. RESULTS: The analysis included 44 cases and 220 matched controls (mean age, 82 years). Ever use of bisphosphonates was more frequent in cases than controls (29.6% vs 10.5%). In multivariate analyses, OR (95% CI) of atypical femoral fracture was 4.30 (1.55 to 11.9) in ever versus never users of bisphosphonates. The risk increased with long-term use, with an OR of 9.46 (2.17 to 41.3) comparing those using bisphosphonates over 3 years versus no users (p for trend=0.01). CONCLUSIONS: Bisphosphonate use was associated with an increased risk of subtrochanteric or diaphyseal fractures in elderly women in a low fracture risk population, with a higher risk among long-term bisphosphonate users.